Achieving the innovative edge in technology, engineering design, and entrepreneurship - Robert M. Pech (Journal of Innovation and Entrepreneurship, 2016)
Disruptive and radical innovations can lead to achieving a competitive edge in technology, design engineering, and entrepreneurship. Likewise, entrepreneurship can encourage more innovation. This article highlights the inter-relationships between these forces and how one can inform and action the others. By examining diverse industries such as Hewlett-Packard; Little Swan of China; Rip Curl, the surfing company of Australia; and others as case studies, and numerous other practical examples appropriately selected from across the last century, the role of technology and design in advancing products and services in the commercial arena is exemplified and demonstrates that there are common patterns over time in which technological and managerial advancements play unique and vital roles in driving markets. The article also identifies the key characteristics of disruptive technologies and those of successful innovative engineers, as well as those of successful entrepreneurs in the field of technology and engineering by examining their approaches and methods to serve as catalysts for future innovators who set their sights on starting up their own venture.
Keywords: 650; Disruptive innovation; Design engineering; Closed and open innovation; New venture; Intellectual property; Niche; Dominant model; Social (or philanthropic) entrepreneurship